Development of an efficient voltage regulation mechanism for switched capacitor converter with exponential gain - Abdul Kadir, Mohamed N.; Ameen, Yasir M. Y.; Al-Badrani, Harith (Eastern-European Journal of Enterprise Technologies, 2022)
The compact switched-capacitor converter with exponential gain and modular design has been adopted in this paper. Two approaches have been applied to improve the efficiency by providing multiple no-load voltages. The first modifies the switching strategy to bypass the gain of one or more stages. The second introduces modified design that provide additional no-load voltages through alternative current paths. The voltage regulation is implemented by two control loops: The outer loop is designed to produce the minimum feasible no-load voltage and the inner loop adjusts the duty ratio of the switching signals to regulate the voltage to meet the desired reference. Switched capacitor converters have been used as voltage multipliers with constant voltage gain. The efficiency of a switched capacitor converter depends on the ratio between regulated to unregulated output voltage. Therefore, output voltage adjustment of these converters causes a significant efficiency reduction. By providing multiple no-load voltages within the output voltage range the efficiency of the switched capacitor converter can be improved. The proposed design has been applied to a three-stage converter to provide six no-load voltages. Simulation results demonstrate that the average efficiency over the entire output voltage range is more than 90 % of its maximum efficiency of the unregulated switched capacitor converter which reflects the effectiveness of the proposed scheme. This paper offers an efficient method to regulate the voltage of a modular switched capacitor converter with exponential gain. The advantages of the proposed design are small number of added components, does not require additional sources and suitable for higher power range